An overview of environmental excellence models - Lukáš Vartiak (Economic and Environmental Studies (E&ES), 2016)
Companies use many managerial frameworks that ensure desired development. Some of these frameworks are quality-oriented, others are financially-oriented but only a few of them are environmentallyoriented. The aim of the paper is to delineate selected environmental excellence models on account of their comparison. The main motive for the selection of the paper's topic were researches conducted by various authors who have dealt with environmental excellence models, respectively with self-assessment based on existing environmental excellence models. To fulfil the aim of the paper, secondary research is to be conducted. Based on the methods of analysis, comparison and selection, the most frequently occurring criteria of analysed environmental excellence models are to be identified. As a main finding may be considered that three of four environmental excellence models consist of various criteria, while most of these criteria are similar. However, criteria based on another important principles are not included in more than one of mentioned environmental excellence models. This obliges to further research aimed at developing an integrated environmental excellence model consisting of the most important criteria.
Keywords: N50 : Q56; 330; business excellence; environment; quality; model; environmental excellence models